2013
DOI: 10.1111/isqu.12078
|View full text |Cite
|
Sign up to set email alerts
|

Portraying the Global: Cross-national Trends in Textbooks’ Portrayal of Globalization and Global Citizenship

Abstract: Many have noted the rise of the global in academic and popular discourse. We ask how this global frame of reference has been incorporated into secondary social science textbooks, a realm traditionally dominated by nationalist discourse. Utilizing a data set from more than 500 secondary school textbooks from around the world, spanning 1970-2008, we describe the incorporation of mentions of globalization and global citizenship into textbooks over time and then use a multilevel model to determine the textbook and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Given that textbooks have to cover a broad range of topics, this is indicative of the prevalence (and political power) of the term in the twenty-first century (Bhatia, 2005). Drawing on the analysis of school textbooks, the Stanford Group claims that politically relevant concepts increasingly diffuse across the international realm, hence indicating the emergence of a world society (Buckner & Russell, 2013;Ramirez et al, 2009). In principal, my findings are in line with such claims.…”
Section: Prevalence and Definitions Of Terrorism In The School Textbookssupporting
confidence: 63%
“…Given that textbooks have to cover a broad range of topics, this is indicative of the prevalence (and political power) of the term in the twenty-first century (Bhatia, 2005). Drawing on the analysis of school textbooks, the Stanford Group claims that politically relevant concepts increasingly diffuse across the international realm, hence indicating the emergence of a world society (Buckner & Russell, 2013;Ramirez et al, 2009). In principal, my findings are in line with such claims.…”
Section: Prevalence and Definitions Of Terrorism In The School Textbookssupporting
confidence: 63%
“…Modern day media technology transgresses geopolitical borders or what we often regard as sovereign territory, and according to Buckner and Russell (2013), ''the rise of discourses surrounding globalisation and global citizenship may shift focus away from a nation-dominant narrative toward a global narrative, which may imply a fundamental reconceptualisation of the nation-state's purpose or identity'' (p. 738). It may also imply understanding ourselves as part of a global citizenship with rights to freely traverse borders and politics.…”
Section: Freedom Of Information Versus Surveillance Of Information Tementioning
confidence: 99%
“…However, over time, more countries have shifted to a more global-focused civics curriculum (Ramirez, Meyer, & Wotipka, 2009). In addition to documenting a worldwide rise in textbook foci on global citizenship since the 1970s, Buckner and Russell (2013) found that, in the 2000s, 89% of their analysed books also discussed national citizenship, suggesting that global citizenship discourse did not necessarily replace notions of national citizenship. Latin America and the Caribbean stand out, with especially high rates: in the last two decades, around half the books 0 .…”
Section: Global Citizenshipmentioning
confidence: 99%